Impact of financial literacy on investment performance of individual household investors in the Jaffna district of Sri Lanka - Anandasayanan, S. (University of Jaffna, 2024)
The increased complexity of the financial markets with different types of financial products has generated the need to examine the role of financial literacy in the investment affairs of individuals. Financial literacy is the capability of individuals to evaluate complex financial products based on their investment needs and goals and to select the financial products which are appropriate to them. This study aims to examine the impact of financial literacy on investment performance of household investors in the Jaffna District of Sri Lanka. Questionnaire is the major source of data for the study. Financial literacy level of the households was measured on the basis of the constructs of financial attitude, financial behavior, and financial knowledge and investment performance was measured in terms of return-based investment performance and non-return-based performance. The sampling method occupied in the study is proportionate stratified random sampling method and the sample size is 922. The regression analysis was carried out to identify the effect of financial literacy on investment performance. The results of the study reveal that financial literacy level of household investors in the Jaffna District has significant positive impact on investment performance of them (R=0.4719). Financial literacy supports investors in setting realistic investment goals, identifying their own risk tolerance level, understanding investment options available in the financial markets, assessing risk, return and other features of different investment options, diversifying their investment portfolio and making informed choices to grow their wealth. Therefore, the outcomes from the investments of the household investors can be improved by taking necessary measures by relevant authorities to promote the financial literacy level of them.
Keywords: Financial Literacy; Financial Attitude; Financial Behavior; Financial Knowledge; Investment Performance